2007
DOI: 10.1111/j.1600-0838.2006.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity training dissociates metabolic from aerobic fitness

Abstract: This study investigated the effect of prolonged whole-body low-intensity exercise on blood lipids, skeletal muscle adaptations and aerobic fitness. Seven male subjects completed a 32-day crossing of the Greenland icecap on cross-country skies and before and after this arm or leg cranking was performed on two separate days and biopsies were obtained from arm and leg muscle, and venous blood was sampled.During the crossing, subjects skied for 342 AE 42 min/day and body mass was decreased by 7.1 AE 0.7 kg. Peak l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Data from Helge et al suggest that exercise at low workload for several weeks could also modify fuel selection during exercise, but the direction of these changes was different in these two studies conducted during 48- (Helge et al 2003) and 38-day ski treks (Helge et al 2008) in four and seven subjects, respectively. In both studies the respiratory exchange ratio (RER) was measured during 10-or 15-min arm cranking (at 40-50 and 100 W) and cycling exercise (at 100 and 200 W).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Data from Helge et al suggest that exercise at low workload for several weeks could also modify fuel selection during exercise, but the direction of these changes was different in these two studies conducted during 48- (Helge et al 2003) and 38-day ski treks (Helge et al 2008) in four and seven subjects, respectively. In both studies the respiratory exchange ratio (RER) was measured during 10-or 15-min arm cranking (at 40-50 and 100 W) and cycling exercise (at 100 and 200 W).…”
Section: Introductionmentioning
confidence: 94%
“…These changes in the capacity to transport plasma glucose into muscle fibers could favor plasma glucose oxidation and a shift to carbohydrate (CHO) oxidation during prolonged exercise at low workload particularly in subjects supplemented with CHO both before and during exercise. However, in the experiment by Helge et al (2003Helge et al ( , 2008 plasma glucose oxidation was not measured and the subjects were studied following an overnight fast which favors fat oxidation particularly at low workload (Achten and Jeukendrup 2003). The putative metabolic adaptations brought about by several week of prolonged exercise at low workload with a ''continuous pattern of eating'' (Westerterp 2001) could be more pronounced in subjects supplemented with CHO than in a fasting state.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also executed some biopsies from arm and leg muscle, and venous blood. They concluded that the exercise could improve the people's performance since an improved blood lipid profile and thus metabolic fitness appeared after prolonged low-intensity training and this occurred despite a decreased aerobic fitness and an unchanged arm and leg muscle hormone-sensitive lipase activity (Helge et al, 2008) Einspruch (1996) explained how challenge of providing rehabilitative services at relatively low price could help companies increase their productivities. They study also explains that if there is a link between the company' objectives and customer satisfaction, it is imperative to evaluate quality or customer satisfaction in the context of the patient's experience and described the quality function deployment system and how it could lead to a better understanding of the customer's needs and wants.…”
Section: Introductionmentioning
confidence: 99%
“…They also executed some biopsies from arm and leg muscle, and venous blood. They concluded that the exercise could improve the people's performance since an improved blood lipid profile and thus metabolic fitness appeared after prolonged low-intensity training and this occurred despite a decreased aerobic fitness and an unchanged arm and leg muscle hormone-sensitive lipase activity (Helge et al, 2008) Einspruch (1996 explained how challenge of providing rehabilitative services at relatively low price could help companies increase their productivities. They study also explains that if there is a link between the company' objectives and customer satisfaction, it is imperative to evaluate quality or customer satisfaction in the context of the patient's experience and described the quality function deployment system and how it could lead to a better understanding of the customer's needs and wants.…”
Section: Introductionmentioning
confidence: 99%